2020
DOI: 10.1002/cbic.201900646
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chemistry in the Biomembrane

Abstract: The combination of supramolecular functional systems with biomolecular chemistry has been a fruitful exercise for decades, leading to a greater understanding of biomolecules and to a great variety of applications, for example, in drug delivery and sensing. Within these developments, the phospholipid bilayer membrane, surrounding live cells, with all its functions has also intrigued supramolecular chemists. Herein, recent efforts from the supramolecular chemistry community to mimic natural functions of lipid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 184 publications
(129 reference statements)
0
15
0
2
Order By: Relevance
“…4 Giant unilamellar vesicles (GUVs, diameter > 1 µm) offer the benefit that individual vesicles are directly observable by microscopy but are typically less stable than LUVs. 5 Ion channels are often also studied using planar lipid bilayer techniques, in which a bilayer is formed across a micrometre scale aperture that separates chambers filled with aqueous solutions. Single channel electrical recordings of the ion current through a membrane channel is used to characterise the ion transport capability of the system.…”
Section: Molecular Recognition and Sensing At A Bilayer Interface Using Membrane-bound Receptors Experimental Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Giant unilamellar vesicles (GUVs, diameter > 1 µm) offer the benefit that individual vesicles are directly observable by microscopy but are typically less stable than LUVs. 5 Ion channels are often also studied using planar lipid bilayer techniques, in which a bilayer is formed across a micrometre scale aperture that separates chambers filled with aqueous solutions. Single channel electrical recordings of the ion current through a membrane channel is used to characterise the ion transport capability of the system.…”
Section: Molecular Recognition and Sensing At A Bilayer Interface Using Membrane-bound Receptors Experimental Techniquesmentioning
confidence: 99%
“…7 A detailed discussion of the various experimental techniques available is beyond the scope of this perspective, and we direct the reader to a number of review articles on the subject. 3,5 Molecular recognition and sensing at a bilayer interface using membrane-bound receptors Confinement of supramolecular receptors within a lipid bilayer membrane leads to an increase in effective concentration by many orders of magnitude, because the receptors are confined to the volume of the membrane. For example, in a typical fluorescence ion transport assay, a total concentration of receptor (ion carrier) of 100 nM in vesicles with lipid concentration of 100 μM experiences an effective concentration in the membrane of ~1 mM, because the membrane-embedded carrier occupies only a small volume fraction of the solution that comprises the lipid membrane.…”
Section: Molecular Recognition and Sensing At A Bilayer Interface Using Membrane-bound Receptors Experimental Techniquesmentioning
confidence: 99%
“…[1][2][3][4][5] A key requirement for the development of proto-cellular entities is chemical communication between the internal and external compartments. Signalling processes across lipid bilayers can be activated through mechanisms involving either transduction of chemical signals [6][7][8][9][10] or exchange of active components between the two sides of a membrane. [11][12][13][14][15][16][17][18][19] Synthetic systems inspired by transmembrane protein receptors have been developed to control the generation of a compartmentalized signal in response to a specic molecular recognition event.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tweezers have never been exploited to activate membrane translocation of K‐rich peptides and proteins. Even more generally, supramolecular host‐guest recognition at biomembrane interfaces still remains largely underexplored [19] …”
Section: Introductionmentioning
confidence: 99%
“…Even more generally,s upramolecular host-guest recognition at biomembrane interfaces still remains largely underexplored. [19] An ideal K-compatible activator should be capable of recognizing K-rich peptides or proteins and interact with membranes.P reviously,w er eported amphiphilic sulfonatocalix [4]arene (sCx4-5C) as ap otent activator for the transport of R-rich CPPs,attributable to the preorganized scaffold of calixarene and its recognition capability. [20] In other studies,itwas reported that calix [5]arene can recognize alkylammonium ions benefiting from its size fit.…”
Section: Introductionmentioning
confidence: 99%